HAK PRIVASI DAN KERAHASIAAN PENYAKIT TERMASUK DATA MEDIS PASIEN DI MASA PANDEMI PERSPEKTIFUNDANG-UNDANG KESEHATAN - Risa Handayani, (2021)
Management of data and information related to the privacy of patient data during the current Covid-19 pandemic must be done well, because it is related to the patient data is regulated by law. This study aims to find out "How to apply the right of privacy and confidentiality of disease in medical data of hospital patients during the Covid-19 pandemic in accordance with Health Law" and "How the sanctions are given to hospitals if they do not meet the confidentiality of the patient's medical data.". The research method used in this writing is normative law research or library research, which is research on secondary data. The results concluded that to open the data recorded in the patient's medical record, the patient's consent had to be obtained. Potential protective laws against patients according to Article 56 and 57 of Health Law carried out preventively to maximize the implementation of medical records and inform consent, while repressive legal protection is in accordance with Article 58 of Health Law , "the health service provider implements it in accordance with the applicable legislation", namely through mediation and if it is proven that medical action is not in accordance with Standard Operating Procedures, compensation will be procured.